Utilization of artificial intelligence (AI) technology in the judicial system - Sandhi, I Gusti Bagus; Farina, Thea; Kristanto, Kiki (Journal of Law Science, 2025)
The utilization of Artificial Intelligence (AI) technology in the Supreme Court represents an innovative step toward modernizing Indonesia’s judicial system. AI offers advantages in efficiently processing legal data, analyzing jurisprudence, and providing legal recommendations to assist judges in decision-making. However, AI implementation in the legal system presents challenges, including regulatory issues, ethical considerations, and AI’s limitations in understanding the humanistic dimensions of legal rulings. This study employs a normative juridical method with a doctrinal approach to analyze the role, benefits, and legal implications of AI usage in Indonesia’s judicial system. The findings indicate that while AI can enhance judicial efficiency, strict regulations are necessary to ensure transparency, accountability, and legal compliance in its application.